Fate by RNA methylation: m(6)A steers stem cell pluripotency - Zhao, Boxuan Simen (Genome Biol, 2015)
The N(6)-methyladenosine (m(6)A) modification of mRNA has a crucial function in regulating pluripotency in murine stem cells: it facilitates resolution of naïve pluripotency towards differentiation.